Mixed infections in tuberculosis: The missing part in a puzzle. (December 2017) - Tarashi, Samira; Fateh, Abolfazl; Mirsaeidi, Mehdi; Siadat, Seyed Davar; Vaziri, Farzam
Abstract: The mixed strains infection phenomenon is a major problem posing serious challenges in control of tuberculosis (TB). In patients with mixed infection, several different strains of Mycobacterium tuberculosis can be isolated simultaneously. Although different genotyping methods and various molecular approaches can be employed for detection of mixed infection in clinical samples, the MIRU-VNTR technique is more sensitive with higher discriminative power than many widely used techniques. Furthermore, the recent introduction of whole genome sequencing (WGS) promises to reveal more details about mixed infection with high resolution. WGS has been used for detection of mixed infection with high sensitivity and discriminatory, but the technology is currently limited to developed countries. Mixed infection may involve strains with different susceptibility patterns, which may alter the treatment outcome. In this report, we review the current concepts of mixed strains infection and also infection involving strains with a different susceptibility pattern in TB. We evaluate the importance of identifying mixed infection for diagnosis as well as treatment and highlight the accuracy and clinical utility of direct genotyping of clinical specimens.